2013
DOI: 10.4141/cjss2013-002
|View full text |Cite
|
Sign up to set email alerts
|

Soil mineral nitrogen responses following liquid hog manure application to semiarid forage lands

Abstract: Bork, E. W., Lambert, B. D., Banerjee, S. and Blonski, L. J. 2013. Soil mineral nitrogen responses following liquid hog manure application to semiarid forage lands. Can. J. Soil Sci. 93: 369–378. Expansion of intensive livestock operations into semiarid regions lacking cultivated lands requires consideration of perennial forages for the efficient and sustainable disposal of manure. Little information exists on the nutrient dynamics associated with the application of manure to these areas. We examined soil mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A similar study showed that IM increased subsequent corn yield for both CC and DC (Milliron et al., 2019), possibly due to their lower manure application rate or possibly greater soil N stores at our location. Injected manure could have conserved more manure N in the soil (Bierer, Maguire, Strickland, Thomason, & Stewart, 2017; Bork, Lambert, Banerjee, & Blonski, 2013; Milliron et al., 2019) or in belowground rye biomass allowing for a greater N pool that could provide nutrients to the subsequent corn crop. To evaluate the effect of fall manure management on the subsequent corn, we did not apply additional N in spring to corn in any of the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that IM increased subsequent corn yield for both CC and DC (Milliron et al., 2019), possibly due to their lower manure application rate or possibly greater soil N stores at our location. Injected manure could have conserved more manure N in the soil (Bierer, Maguire, Strickland, Thomason, & Stewart, 2017; Bork, Lambert, Banerjee, & Blonski, 2013; Milliron et al., 2019) or in belowground rye biomass allowing for a greater N pool that could provide nutrients to the subsequent corn crop. To evaluate the effect of fall manure management on the subsequent corn, we did not apply additional N in spring to corn in any of the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that manure applied in late versus early fall resulted in smaller flow‐weighted NO 3 –N concentrations in tile‐drainage during the subsequent spring (van Es et al, 2006) or less soil NO 3 –N at deep soil depths (31–60 cm and 61–90 cm) in spring (Vetsch et al, 2017) suggesting reduced risk of NO 3 –N leaching. In addition, Bork et al (2013) found that soil mineral N (NO 3 and NH 4 ) was increased by 35% when liquid hog manure was injected compared to surface applied on a perennial native grassland. In a laboratory study, Bierer et al (2017) also reported that injection of dairy slurry compared to surface application increased soil NO 3 –N by 23% in a clay loam and 110% in a sandy loam.…”
Section: Discussionmentioning
confidence: 99%